Analytical estimates of front velocity in the frontal polymerization of thermoset polymers and composites. Issue 11 (30th April 2021) - Kumar, Aditya; Gao, Yuan; Geubelle, Philippe H.
Abstract: This note presents approximate analytical expressions for the velocity of the self‐propagating reaction front in the frontal polymerization of thermoset polymers and composites. Prior estimates available in the literature for the front velocity have been limited by their applicability to simple reaction kinetics. The improved estimates provided in this work are shown to be applicable to complex reaction kinetics encountered in the frontal polymerization of neat thermoset polymers or fiber‐reinforced polymer‐matrix composites with a wide range of polymer chemistries, including dicyclopentadiene, cyclooctadiene, acrylates, and epoxies. They are also shown to be applicable to wide range of values of the initial temperature and initial degree of cure of the resin, and of the volume fraction of the reinforcing phase. Abstract :